2018
DOI: 10.3390/catal8120646
|View full text |Cite
|
Sign up to set email alerts
|

Mn Modified Ni/Bentonite for CO2 Methanation

Abstract: To enhance the low-temperature catalytic activity and stability of Ni/bentonite catalyst, Ni-Mn/bentonite catalyst was prepared by introducing Mn into Ni/bentonite catalyst and was used for CO 2 methanation. The results indicated that the addition of Mn enhanced the interaction between the NiO and the bentonite carrier, increased the dispersion of the active component Ni and decreased the grain size of the active component Ni, increased the specific surface area and pore volume of the Ni/bentonite catalyst, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 64 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…In the pressure region P/P 0 >0.4, an H3‐type hysteresis loop was generated by capillary condensation in the pores. The above results indicate that the incorporation of nickel on bentonite support causes a decrease in the specific surface area due to partial blockage of mesopores by Ni particles [26,27] …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the pressure region P/P 0 >0.4, an H3‐type hysteresis loop was generated by capillary condensation in the pores. The above results indicate that the incorporation of nickel on bentonite support causes a decrease in the specific surface area due to partial blockage of mesopores by Ni particles [26,27] …”
Section: Resultsmentioning
confidence: 86%
“…The above results indicate that the incorporation of nickel on bentonite support causes a decrease in the specific surface area due to partial blockage of mesopores by Ni particles. [26,27] The study of the oxidation state of elements of Ni/ Bentonite-20-C was done by X-ray photoelectron spectroscopy (XPS) (Figure 4). The survey scan (Figure 4a) exhibited the presence of the respective metals.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The presence of oxygen vacancies was beneficial to the adsorption of CO 2 , which could promote CO 2 activation [23,58]. Jiang et al [17] found that the content of surface oxygen on the Mn promoted Ni/bentonite catalyst was 83.55%, which was higher than that of the unpromoted Ni/bentonite catalyst (74.85%), representing the higher amount of oxygen vacancies. The increased oxygen vacancies were helpful to the adsorption and dissociation of CO 2 on the catalyst.…”
Section: Chemical State Of the Elements On Ni-xsi/zro 2 Catalystsmentioning
confidence: 99%
“…Meanwhile, the heat released during the reaction will lead to the sintering of metal particles and deactivation of the catalysts [9,16]. Therefore, designing a high active and stable catalyst operating at low temperature is important [17].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, all commercial methanation catalysts for SNG production have been Ni-based catalysts due to their high performance and low cost [6][7][8][9][10][11][12][13][14][15][16][17][18]. Nevertheless, the major weaknesses of nickel catalysts include agglomeration of Ni nanoparticles, formation of carbon deposits at higher temperatures, and poor activity at low temperatures (250 • C) for the complete methanation of syngas [19][20][21][22][23][24][25][26][27][28][29][30][31]. The increase in low temperature performance of the Ni catalysts in syngas methanation is critical.…”
Section: Introductionmentioning
confidence: 99%